Effect of Light Intensity and Handling During Rearing on Broiler Breast Meat Characteristics - McKee, N.A.; Lien, R.J.; Hess, J.B.; Bilgili, S.F.; McKee, S.R. (International Journal of Poultry Science, 2009)
This study was designed to evaluate the effects of light intensity and handling during rearing on broiler and meat quality factors. Male broilers were housed in light-tight rooms and subjected to Bright (BL) [15.0 Foot-Candles (FC)] or Dim (DL) (0.1 FC) intensity. To determine effects of handling on meat quality, birds were further divided into 3 handling groups either handling by Legs (L) or Wings (W), or No Handling (NoH). After processing and chilling at 51 d of age, breast filets were deboned at 2 h and 4 h PM and filet weights, filet dimensions (length, width, height and area), sarcomere length, cook-loss and tenderness were evaluated. Birds subjected to DL had greater live weights (p<0.05), post-chill weights and filet weights compared to birds reared in BL. The increase in filet weights observed for in DL was due to an increase in filet length and area. Light or handling treatments had no affect on DPM and other carcass defects. Cook-loss had no specific trend. Filets deboned at 2 h PM had higher shear values than those deboned at 4 h PM, regardless of light or handling. Within the 2 h PM deboning period, DL resulted in an increase in shear values, as well as sarcomere length, compared to BL treatments. This trend was not observed in the filets deboned at 4 h PM. In conclusion, dim light treatment resulted in longer, heavier filets but slightly tougher meat when filets were deboned at 2 h PM.